2022
DOI: 10.1111/jfpp.16586
|View full text |Cite
|
Sign up to set email alerts
|

Seed pumpkin flour as a dietary fiber source in Bologna‐Type sausages

Abstract: Today, consumer awareness and mindfulness of the relationship between consumed food and general health have been increasing. This situation changes the perceptions and purchasing habits of consumers and increases the demand for functional foods. Meat can be considered a functional food in that it contains conjugated linoleic acid and minerals such as iron, zinc, selenium, dipeptides such as carnosine, anserine, creatine, and taurine, vitamins B and E and components including glutathione, ubiquinol, and lipoic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…62 The decrease in the resiliency of the inulin-treated sausage might be due to an increase in hardness values. 63 The results of the present study were similar to findings when pumpkin seed flour was added as a source of dietary fiber in Bologna type sausages 64 and carrot fiber as a binder in cooked sausage. 65 Sharaf Eddin et al 66 posited that the incorporation of Citri-Fi 125 FG citrus fiber supplemented surimi showed the lowest resilience.…”
Section: Texture Profile Analysissupporting
confidence: 86%
“…62 The decrease in the resiliency of the inulin-treated sausage might be due to an increase in hardness values. 63 The results of the present study were similar to findings when pumpkin seed flour was added as a source of dietary fiber in Bologna type sausages 64 and carrot fiber as a binder in cooked sausage. 65 Sharaf Eddin et al 66 posited that the incorporation of Citri-Fi 125 FG citrus fiber supplemented surimi showed the lowest resilience.…”
Section: Texture Profile Analysissupporting
confidence: 86%
“…Pumpkin, a member of the family Cucurbitaceae , is a source of many valuable substances such as protein, dietary fiber, starch, vitamins (A, B1, B2, and C), minerals (Fe, Ca, Na, K, Mg, and P), and carotenoids, which have important effects on human health (Choi, Kim, et al, 2012). Although there are several studies about the use of pumpkin‐based components such as pumpkin (Zargar et al, 2014), pumpkin seed powder (Bulambaeva et al, 2014; Mumyapan et al, 2022) and pumpkin fiber extract (Choi, Kim, et al, 2012; Kim et al, 2016) in sausages and frankfurters production, there are no studies on model‐system beef emulsion. However, the usage of pumpkin as a dietary fiber source in the model‐system beef emulsion is important for the improvement of physicochemical, emulsification, and the textural properties of beef emulsions.…”
Section: Introductionmentioning
confidence: 99%
“…Aslinah et al ( 2018 ) also determined that using adzuki bean flour as a fat replacer in reduced‐fat beef meatballs at high levels caused higher hardness and chewiness, but cohesiveness and springiness were not changed. In another study, Mumyapan et al ( 2021 ) found lower resilience and cohesiveness in bologna‐type sausages produced with different levels of pumpkin seed flour.…”
Section: Resultsmentioning
confidence: 94%
“…In this context, consumers' interest in foods with reduced fat and high fiber content is increasing (El Zeny et al, 2019 ; Modi et al, 2009 ). For this reason, the number of studies on reducing or replacing animal fat in meat products is increasing day by day (Jo et al, 2003 ; Yılmaz & Dağlıoğlu, 2003 ; Serdaroglu & Degirmencioglu, 2004 ; Turhan et al, 2005 ; Pelser et al, 2007 ; Turhan et al, 2007 ; Valencia et al, 2008 ; Bilek & Turhan, 2009 ; Bastos et al, 2014 ; Choi et al, 2016 ; Rabadan et al, 2021 ; Mumyapan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%